Beyond RMSE: The GEDI imputed waveform product minimizes artificial homogeneity evident in existing global forest height maps - Eugene Seo; Sean P. Healey; Zhiqiang Yang; John D. Armston; Ralph O. Dubayah; Simon Ilyushchenko; Tiago De Conto; Matthew G. Betts (Remote Sensing of Environment, 2026)

The next Landsat: Mission turning point? - David P. Roy; Michael A. Wulder; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; Justin Huntington; Volker C. Radeloff; Ted Scambos; Crystal Schaaf; Curtis E. Woodcock; Zhe Zhu (Remote Sensing of Environment, 2026)

Integrating albedo offsets in reforestation decisions for climate change mitigation outcomes in 2050: A case study in the USA - Lucas K. Johnson; Zhiqiang Yang; Angela Erb; Ryan M. Bright; Grant M. Domke; Tracey S. Frescino; Crystal B. Schaaf; Sean P. Healey (Forest Ecology and Management, 2025)

A geostatistical approach to enhancing national forest biomass assessments with Earth Observation to aid climate policy needs - Neha Hunka; Paul May; Chad Babcock; José Armando Alanís de la Rosa; Maria de los Ángeles Soriano-Luna; Rafael Mayorga Saucedo; John Armston; Maurizio Santoro; Daniela Requena Suarez; Martin Herold; Natalia Málaga; Sean P. Healey; et al. (Remote Sensing of Environment, 2025)

Calibration of GEDI footprint aboveground biomass models in Mediterranean forests with NFI plots: A comparison of approaches - Adrián Pascual; Paul B. May; Aarón Cárdenas-Martínez; Juan Guerra-Hernández; Neha Hunka; Jamis M. Bruening; Sean P. Healey; John D. Armston; Ralph O. Dubayah (Journal of Environmental Management, 2025)

Congruent Long‐Term Declines in Carbon and Biodiversity Are a Signature of Forest Degradation - Matthew G. Betts; Zhiqiang Yang; John S. Gunn; Sean P. Healey (Global Change Biology, 2024)
Recent global policy initiatives aimed at reducing forest degradation require practical definitions of degradation that are readily monitored. However, consistent approaches for monitoring forest degradation over the long term and at broad scales are lacking. We quantified the long‐term effects of intensive wood harvest on above‐ground carbon and biodiversity at fine resolutions (30 m 2 ) and broad scales (New Brunswick, Canada; 72,908 km 2 ). Model predictions for above‐ground biomass were highly correlated with independent data ( r = 0.77). After accounting for carbon stored in wood products, net CO 2 emissions from forests for the region from 1985 to 2020 were 141 CO 2 e Tg (4.02 TgCO 2 e year −1 ; 32% of all reported emissions). We found strong positive correlations between locations with declines in above‐ground carbon and habitats for old‐forest bird species, which have lost > 20% habitat over 35 years. High congruence between biodiversity and forest carbon offers potential for policy incentives to conserve both objectives simultaneously and slow rates of forest degradation. These methods could be used to track forest degradation for managed forest regions worldwide.

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Spatial heterogeneity of global forest aboveground carbon stocks and fluxes constrained by spaceborne lidar data and mechanistic modeling - Lei Ma; George Hurtt; Hao Tang; Rachel Lamb; Andrew Lister; Louise Chini; Ralph Dubayah; John Armston; Elliott Campbell; Laura Duncanson; Sean Healey; Jarlath O'Neil‐Dunne; et al. (Global Change Biology, 2023)
Forest carbon is a large and uncertain component of the global carbon cycle. An important source of complexity is the spatial heterogeneity of vegetation vertical structure and extent, which results from variations in climate, soils, and disturbances and influences both contemporary carbon stocks and fluxes. Recent advances in remote sensing and ecosystem modeling have the potential to significantly improve the characterization of vegetation structure and its resulting influence on carbon. Here, we used novel remote sensing observations of tree canopy height collected by two NASA spaceborne lidar missions, Global Ecosystem Dynamics Investigation and ICE, Cloud, and Land Elevation Satellite 2, together with a newly developed global Ecosystem Demography model (v3.0) to characterize the spatial heterogeneity of global forest structure and quantify the corresponding implications for forest carbon stocks and fluxes. Multiple‐scale evaluations suggested favorable results relative to other estimates including field inventory, remote sensing‐based products, and national statistics. However, this approach utilized several orders of magnitude more data (3.77 billion lidar samples) on vegetation structure than used previously and enabled a qualitative increase in the spatial resolution of model estimates achievable (0.25° to 0.01°). At this resolution, process‐based models are now able to capture detailed spatial patterns of forest structure previously unattainable, including patterns of natural and anthropogenic disturbance and recovery. Through the novel integration of new remote sensing data and ecosystem modeling, this study bridges the gap between existing empirically based remote sensing approaches and process‐based modeling approaches. This study more generally demonstrates the promising value of spaceborne lidar observations for advancing carbon modeling at a global scale.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Supporting National Forest System Planning with Forest Inventory and Analysis Data - Zachary Wurtzebach; R Justin DeRose; Renate R Bush; Sara A Goeking; Sean Healey; Jim Menlove; Kristen A Pelz; Courtney Schultz; John D Shaw; Chris Witt (Journal of Forestry, 2020)
In 2012, the US Forest Service promulgated new regulations for land-management planning that emphasize the importance of scientifically credible assessment and monitoring strategies for adaptive forest planning and the maintenance or restoration of ecological integrity. However, in an era of declining budgets, the implementation of robust assessment and monitoring strategies represents a significant challenge for fulfilling the intent of the new planning rule. In this article, we explore opportunities for using data and products produced by the USDA Forest Service’s Forest Inventory and Analysis (FIA) Program to support the implementation of the 2012 Planning Rule. FIA maintains a nationally consistent statistical sample of field plots that covers most national forests with hundreds of plots. We suggest that leveraging FIA data and products can generate efficiencies for assessment, planning, and monitoring requirements detailed in the 2012 Planning Rule, and help fulfill the adaptive intent of the new planning rule. However, strong national leadership and investment in regional-level analytical capacity, FIA liaisons, and decision-support tools are essential for systematically realizing the benefits of FIA data for forest planning across the National Forest System.

Geographic and temporal variations in turbulent heat loss from lakes: A global analysis across 45 lakes - R. Iestyn Woolway; Piet Verburg; John D. Lenters; Christopher J. Merchant; David P. Hamilton; Justin Brookes; Elvira de Eyto; Sean Kelly; Nathan C. Healey; Simon Hook; Alo Laas; Don Pierson; et al. (Limnology and Oceanography, 2018)
Heat fluxes at the lake surface play an integral part in determining the energy budget and thermal structure in lakes, including regulating how lakes respond to climate change. We explore patterns in turbulent heat fluxes, which vary across temporal and spatial scales, using in situ high‐frequency monitoring data from 45 globally distributed lakes. Our analysis demonstrates that some of the lakes studied follow a marked seasonal cycle in their turbulent surface fluxes and that turbulent heat loss is highest in larger lakes and those situated at low latitude. The Bowen ratio, which is the ratio of mean sensible to mean latent heat fluxes, is smaller at low latitudes and, in turn, the relative contribution of evaporative to total turbulent heat loss increases toward the tropics. Latent heat transfer ranged from ~ 60% to > 90% of total turbulent heat loss in the examined lakes. The Bowen ratio ranged from 0.04 to 0.69 and correlated significantly with latitude. The relative contributions to total turbulent heat loss therefore differ among lakes, and these contributions are influenced greatly by lake location. Our findings have implications for understanding the role of lakes in the climate system, effects on the lake water balance, and temperature‐dependent processes in lakes.

Assessing the Effects of Fire Disturbances and Timber Management on Carbon Storage in the Greater Yellowstone Ecosystem - Feng Zhao; Sean P. Healey; Chengquan Huang; James B. McCarter; Chris Garrard; Sara A. Goeking; Zhiliang Zhu (Environmental Management, 2018)

Forest sector carbon analyses support land management planning and projects: assessing the influence of anthropogenic and natural factors - Alexa J. Dugan; Richard Birdsey; Sean P. Healey; Yude Pan; Fangmin Zhang; Gang Mo; Jing Chen; Christopher W. Woodall; Alexander J. Hernandez; Kevin McCullough; James B. McCarter; Crystal L. Raymond; et al. (Climatic Change, 2017)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Observation of Trends in Biomass Loss as a Result of Disturbance in the Conterminous U.S.: 1986–2004 - Scott L. Powell; Warren B. Cohen; Robert E. Kennedy; Sean P. Healey; Chengquan Huang (Ecosystems, 2014)

Maintaining the confidentiality of plot locations by exploiting the low sensitivity of forest structure models to different spectral extraction kernels - Sean P. Healey; Elizabeth Lapoint; Gretchen G. Moisen; Scott L. Powell (International Journal of Remote Sensing, 2011)

There is more to GIS than Making Maps - Sean P. Healey (Journal of Forestry, 2010)

Underestimating Risks to the Northern Spotted Owl in Fire‐Prone Forests: Response to Hanson et al. - THOMAS A. SPIES; JAY D. MILLER; JOSEPH B. BUCHANAN; JOHN F. LEHMKUHL; JERRY F. FRANKLIN; SEAN P. HEALEY; PAUL F. HESSBURG; HUGH D. SAFFORD; WARREN B. COHEN; REBECCA S.H. KENNEDY; ERIC E. KNAPP; JAMES K. AGEE; et al. (Conservation Biology, 2010)

Combining satellite imagery with forest inventory data to assess damage severity following a major blowdown event in northern Minnesota, USA - Mark D. Nelson; Sean P. Healey; W. Keith Moser; Mark H. Hansen (International Journal of Remote Sensing, 2009)

The Relative Impact of Harvest and Fire upon Landscape-Level Dynamics of Older Forests: Lessons from the Northwest Forest Plan - Sean P. Healey; Warren B. Cohen; Thomas A. Spies; Melinda Moeur; Dirk Pflugmacher; M. German Whitley; Michael Lefsky (Ecosystems, 2008)

Recent History of Large-Scale Ecosystem Disturbances in North America Derived from the AVHRR Satellite Record - Christopher Potter; Pang-Ning Tan; Vipin Kumar; Chris Kucharik; Steven Klooster; Vanessa Genovese; Warren Cohen; Sean Healey (Ecosystems, 2005)